2013
DOI: 10.1016/j.biopsych.2013.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Indiscriminate Amygdala Response to Mothers and Strangers After Early Maternal Deprivation

Abstract: Background In altricial species, maternal stimuli have powerful effects on amygdala development and attachment-related behaviors. In humans, maternal deprivation has been associated with both “indiscriminate friendliness” towards non-caregiving adults and altered amygdala development. We hypothesized that maternal deprivation would be associated with reduced amygdala discrimination between mothers and strangers and increased parent report of indiscriminate friendliness behaviors. Methods 67 youths [33 previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 62 publications
(82 reference statements)
8
82
0
3
Order By: Relevance
“…(consistent with EEG findings obtained by Tarullo et al, 2011); we have no specific hypothesis regarding the group of inhibited children. Our third, primary prediction concerns face familiarity effects, with expectations also based on prior research FinallyRegarding face familiarity effects, in line with our own and others' previous findings (XXX 2015;Olsavsky et al, 2013): Only institutionalized children with IB will fail to discriminate, at the neural level, the face of a stranger and that of a caregiver, not institution-reared children showing atypical, inhibited behavior or family-reared children. Our single secondary-and methodologicalprediction is that hypothesis just advanced will be supported irrespective of whether IB classification is based on observation or caregiver report.…”
Section: Current Studysupporting
confidence: 83%
“…(consistent with EEG findings obtained by Tarullo et al, 2011); we have no specific hypothesis regarding the group of inhibited children. Our third, primary prediction concerns face familiarity effects, with expectations also based on prior research FinallyRegarding face familiarity effects, in line with our own and others' previous findings (XXX 2015;Olsavsky et al, 2013): Only institutionalized children with IB will fail to discriminate, at the neural level, the face of a stranger and that of a caregiver, not institution-reared children showing atypical, inhibited behavior or family-reared children. Our single secondary-and methodologicalprediction is that hypothesis just advanced will be supported irrespective of whether IB classification is based on observation or caregiver report.…”
Section: Current Studysupporting
confidence: 83%
“…However, PI youths exhibited on average greater indiscriminate friendliness behaviors (despite showing no group differences in attachment to parents), which was more pronounced the later a youth was adopted. They also exhibited indiscriminate amygdala reactivity to photos of both their (adoptive) mothers and to strangers (Olsavsky, et al, 2013). PI youth with lower indiscriminate friendliness scores showed more typical amygdala discriminations between mother and stranger.…”
Section: The Development Of Affective Behaviors (Humans)mentioning
confidence: 96%
“…Youths who have been institutionalized and suffer emotional deprivation, who are later adopted by families in the U.S., show a difference in amygdala response when compared to youths who had been raised by their biological parents without emotional deprivation. The youths, who were 4-17 years of age at the time of the imaging study, were shown pictures of their mothers (biological or adopted mothers in the case of the adopted youths; Olavsky et al, 2013). The youths who were raised by their mothers from birth showed significant amygdala responses to their mothers but not to strangers.…”
mentioning
confidence: 99%